Use of whey protein for encapsulation and controlled release of probiotic from protein microencapsule in ex vivo porcine gastrointestinal contents - Nguyen Thi My, Le; Hieu, Nguyen Van (Vietnam Journal of Science and Technology, 2018)
The aim of this study was to evaluate the efficacy of whey protein isolate (WPI) as an encapsulation matrix for improvement of L. fermentum 39-183 viability to low pH and bile and releasing the encapsulated bacteria in ex vivo porcine gastrointestinal (GI) contents. 1g of protein microcapsules (≈ 108 CFU of L. fermentum 39-183 or E. coli GFP+) were incubated in ex vivo porcine GI contents (9 mL) under anaerobic conditions at 370C. Results showed that there was higher than 86% cell survival for encapsulated L. fermentum 39-183 after 3 h incubation in pH 2.0, whereas free cell experienced complete viability loss. Encapsulated L. fermentum 39-183 showed only about 0.86 log reduction for all bile salt levels tested (0.5 ÷ 2.0%), while 3.34 log decrease of free cell after 6 h of incubation. There was almost a complete release (3.9 x 108 CFU) of microencapsulated bacteria in the ileal contents within 2 h, while there was no significant release of encapsulated bacteria in the gastric contents even after 8 h of incubation. This study led to the development and design of a protein capsulation for reinforced probiotic protection during the stressful conditions of gastric and controlled release at a defined location.